Influence of hydrocolloids addition (carboxymethylcellulose and guargum) on some quality attributes of wheat and high quality cassava flour and its bread making potentials - Olatidoye, Olawale Paul (Array, 2020)
High quality cassava flour (HQCF) is now widely used production of baked foods in Nigeria but bread quality is impaired when it is used in the bread formulation. In order to overcome this problem, six breads samples were produced from wheat/HQCF/hydrocolloid:T0100%wheat flour(control);T190:9:CMC;T290:9:GG;T3,80:18:CMC;T4,80:18:GG;T570:27:CMC;T670:27:GG. The flour blends were analyzed for functional, colour and pasting properties while breads characteristics and sensory evaluation were performed in order to assess effect of hydrocolloids on bread. The results showed composite flour with hydrocolloids had the highest bulk density (0.704g/ml), water absorption capacity (2.98m/g), least gelation concentration (4.4g/g), oil absorption capacity (0.71m/g), while control had the highest swelling capacity (1.68g/g). Significant differences at p<0.05 were found on the pasting properties of addition of hydrocolloids with lower pasting temperature (71oC) and time (6.08 min). Bread quality attributes such as loaf volume, specific loaf volume, oven spring, crust colour, crumb colour and firmness of the fresh breads significantly improved with the addition of hydrocolloids compared with bread produced without improvers. The results show that high quality cassava flour could be incorporated up to 18% with carboxymethylcellulose at 2% level without affecting its overall acceptability and thereby enhance the potential for using locally produced flours in bread baking. Sensory score of bread from the addition of hydrocolloids were all acceptable by the panelist. The addition of hydrocolloids could be used as an effective means of improving the quality of gluten free bread.